Transgender Personality Reflected in Buffalo Bill’s Character as Seen in Harris’ `The Silence of The Lambs` - Putri Ganef Pratama; Samanik Samanik (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
This research discusses transgender phenomenon as seen in Thomas Harris‟ novel entitle The Silence of the Lambs. The main purpose of this research is to reveal the Transgender symptoms in the novel through the main character Buffalo Bill. Transgender is a term of which one who fantasies being a woman or man by wearing woman or man dress and make gestures like woman or man. Transgender occurs because his or her background phenomenon of life. The writer arranges the literary review by discussing theory and approach. The theory that the writer applies is queer theory developed by Michael Foucault. Besides, the writer uses the theory of Judith Buttler that explains and describes about sex, orientation and gender. This queer theory is more correlated and understandable for the analysis. In addition, Psychology Literature approach by Ramajaru is also applied. The Result of this analysis shows some symptoms that exist in the character of Buffalo Bill. It was started with cross-dressing, assertion that transgender vital body parts are disgusting, have a desire to change gen types, existence of behavior and physical appearance of inside or abnormal genetic makeup. The writer hopes that by conducting this research it could give the reader more understanding about how is the implementation of queer theory in the literary field or work and become the new guidance to the future reader that are interested in discussing with same theory.